Listening to Charles Ives: Variations on His America - Burkholder, J. Peter (Rowman & Littlefield Publishers, 2021)
Charles Ives is widely regarded as the first great American composer of classical music. But listening to his music is an adventure—hearing how a piece begins may not prepare you for what comes next, or how it ends. Knowing one Ives piece may not prepare you for another. Award-winning music historian J. Peter Burkholder provides an introduction to the composer’s diverse musical output and unusual career to readers of any background, discussing about forty of the best and most characteristic pieces framed with biographical sketches. Burkholder shows how Ives mastered each tradition he encountered, from American popular music to classical European genres, from Protestant church music to his own unique experimental idiom, and then interwove elements from all these traditions in the astonishing works of his maturity. Listening to Charles Ives contains compelling walkthroughs of select pieces and ultimately reveals that there is an Ives piece for everyone.